2020
DOI: 10.1177/2633494120906882
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory abstinence in semen analysis: does it make any sense?

Abstract: Background: The precise effect of ejaculatory abstinence on semen parameters is highly debatable, especially among subfertile men. Previous studies on effect of abstinence time on different semen parameters have reported controversial results. The aim of this study was to retrospectively assess the variance of semen parameters with different periods of ejaculatory abstinence among both a population of normozoospermic ( n = 1621) and oligozoospermic ( n = 416) Tamil men, presenting to a fertility clinic for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…This was true for oligozoospermic men as well. Dupesh et al [47] reported that < 24 h abstinence in oligozoopermic men had highest percentage of progressively motile sperm and normal morphology. However, these studies reported lower sperm count and volume.…”
Section: Sexual Abstinencementioning
confidence: 99%
“…This was true for oligozoospermic men as well. Dupesh et al [47] reported that < 24 h abstinence in oligozoopermic men had highest percentage of progressively motile sperm and normal morphology. However, these studies reported lower sperm count and volume.…”
Section: Sexual Abstinencementioning
confidence: 99%
“…The abstinence time reported in the studies varied from less than a day (in 12 studies, with as short a time as 40 min [ 38 ]) to as long as 30 days or more [ 33 ]. The majority of studies (18 out of 24) compared the effect of short abstinence period (SAP; <2 days) with the WHO-recommended abstinence period (RAP; within 2 to 7 days) on sperm parameters or clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
“…4 It is now becoming clear that this concept cannot always be transposed to infertility clinical outcomes. [24][25][26] A large retrospective study that compared a long abstinence period (>7 days) with a standard abstinence period (2-7 days) reported significantly higher progressive motility and clinical outcomes in the second group. Within the latter, live birth rate was significantly higher in a subgroup of 2-4 days abstinence compared with the first group.…”
Section: Discussionmentioning
confidence: 99%
“…Indications regarding the length of the abstinence were mainly deduced from data reported from diagnostic semen analysis 4 . It is now becoming clear that this concept cannot always be transposed to infertility clinical outcomes 24–26 . A large retrospective study that compared a long abstinence period (>7 days) with a standard abstinence period (2–7 days) reported significantly higher progressive motility and clinical outcomes in the second group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation